Development and pilot data for an app‐based cognitive assessment for detecting memory and executive functioning changes in aging and pre‐clinical AD. (31st December 2021) - Mechanic‐Hamilton, Dawn; Lydon, Sean; Miller, Alex; Halberstadter, Kimberly; DiCalogero, Michael; Wolk, David A.
Abstract: Background: Mobile, valid and engaging cognitive assessments are essential for detecting and tracking change in research participants and patients at risk for Alzheimer's Disease and Related Dementias (ADRDs). This pilot study aims to determine the feasibility and psychometric properties of app‐based memory and executive functioning tasks included in the mobile cognitive app performance platform (mCAPP), to detect cognitive changes associated with aging and preclinical Alzheimer's Disease (AD). Method: The mCAPP includes three gamified tasks: (1) a memory task that includes learning and matching hidden card pairs and incorporates increasing memory load, pattern separation features (lure vs. non‐lure), and spatial memory (2) a stroop‐like task ("brick drop") with speeded word and color identification and response inhibition components and (3) a digit‐symbol coding‐like task ("space imposters") with increasing pairs and incidental learning components. The cohort is also assessed with the NACC UDS3 or T‐Cog neuropsychological battery within six months of the mCAPP testing. Participants included nine older adults (44% female; age=73.9±5.4, years of education=16.6±2.3; 77% Caucasian) with normal cognition who are enrolled in the Penn ADRC cohort. In addition to in‐lab testing, a cohort of participants will also use the mCAPP at home for two weeks and remotely collected data will be presented. Result: On the brick drop task, performance was significantly slower and less accurate on the inhibition task compared to the word and color identification tasks (p<.05). On the space imposters task, increased reaction time and decreased accuracy was observed as the number of digit‐symbol pairs increased, but the difference was not significant. Correlations with UDS 3.0 measures showed significant relationships between the brick drop word/color identification and trail making test A (TMTA) and category fluency (p<.05) as well as between the response inhibition task and category fluency and olfactory function (p<.05). The space imposters task correlated with the TMTA (p<.05). Data will also be presented on home‐based collection of all three mCAPP tasks. Conclusion: This pilot study shows feasibility and validity of app‐based tests of executive functioning and will also examine detection of subtle cognitive differences associated with preclinical AD through burst testing, home‐based data collection and on all three mCAPP measures.